Pemecahan Sertifikat Hak atas Tanah yang Sedang Dibebani Hak Tanggungan - I Putu Gian Favian Adhi Pradana; I Made Suwitra; I Ketut Sukadana (Jurnal Preferensi Hukum, 2020)
The purpose of the procedure for certificate management is still bound by mortgage rights, namely to provide legal protection for creditors, if there is a certificate holder, all of the breakers will be re-burdened according to the loan borrowed. This study aims to look at the legal protection for the bank against land title certificate holders who are encumbered with mortgage rights and legal responsibilities for land title certificates that are encumbered with mortgage rights. This research uses a type of normative legal research, with an invited-invited approach (The Statute Approach) and a conceptual approach. The results showed that the legal protection measures for the bank against the management of land title certificates that were encumbered with mortgage rights could be done by making a power of attorney to charge and making them to sell. In practice, in order to obtain a legal protection against the certainty of the guarantee to be resolved, the Bank will ask permission to make a power of attorney to make the sale. In this case a power of attorney is made to sell by the bank's debtor and can also sell the guarantee. As a result of the legal law, the certificate which is being burdened with a mortgage will be nullified and will be re-burdened on the owner.